Pembuatan Media Pembelajaran untuk Anak Menggunakan Assemblr Studio - Pribadi Ikhsan, Teguh; Anang Kukuh Adisusilo; Nonot Wisnu Karyanto; Lestari Retnawati; Udik Pudjianto (Universitas Wijaya Kusuma Surabaya, 2024)
Learning media is an essential component that supports the success of the learning process, as it influences learning activities and collaborates to achieve educational goals. The elementary school teachers at SD Raudlatul Jannah possess a strong potential in mastering information technology, particularly in creating learning media to enhance classroom activities. This community service activity employs the Multimedia Development Lifecycle (MDLC) method, which integrates various media such as images, animations, audio, and video, focusing on multimedia applications. The PkM team conducted six tests to develop learning media using Assemblr Studio based on Augmented Reality. These tests examined how participants could create educational media by following steps like starting a new project, adding objects, incorporating interactions, building scenes, adding text, and publishing the application